2011
DOI: 10.1074/jbc.m111.237404
|View full text |Cite
|
Sign up to set email alerts
|

Calcium-sensitive Activity and Conformation of Caenorhabditis elegans Gelsolin-like Protein 1 Are Altered by Mutations in the First Gelsolin-like Domain

Abstract: Background:The gelsolin family of actin-severing/capping proteins is calcium-regulated. Results: Two acidic residues of Caenorhabditis elegans gelsolin-like protein 1 (GSNL-1) were important for calcium regulation. Mutation at these residues sensitized GSNL-1 for calcium. Conclusion:The two acidic residues are important to maintain normal calcium sensitivity of GSNL-1. Significance: These residues are conserved, suggesting their importance in calcium regulation of the gelsolin family.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Because synaptic removal is activated during a discrete developmental period, a specific signal is likely required to trigger this pathway. Based on our finding that calcium signaling and UNC-8 function together to promote GABA synapse elimination and previous work that detected roles for calcium in caspase activation and gelsolin function ( Pinan-Lucarre et al, 2012 ; Liu et al, 2011 ), we considered the possibility that these components function in a common pathway and that calcium activates the overall mechanism. To test this idea, we first asked if the cell death gene ced-4 is required for GABA synapse removal in unc-55 mutants in which both DD and VD neurons remodel.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Because synaptic removal is activated during a discrete developmental period, a specific signal is likely required to trigger this pathway. Based on our finding that calcium signaling and UNC-8 function together to promote GABA synapse elimination and previous work that detected roles for calcium in caspase activation and gelsolin function ( Pinan-Lucarre et al, 2012 ; Liu et al, 2011 ), we considered the possibility that these components function in a common pathway and that calcium activates the overall mechanism. To test this idea, we first asked if the cell death gene ced-4 is required for GABA synapse removal in unc-55 mutants in which both DD and VD neurons remodel.…”
Section: Resultsmentioning
confidence: 99%
“…Recent work has shown that functional synaptic components can also be removed by the canonical apoptotic protease, caspase-3 ( Ertürk et al, 2014 ; Wang et al, 2014 ). In C. elegans , the cell death pathway component CED-3/caspase-3 and its upstream regulator CED-4/Apaf1 promote synaptic disassembly by activating the F-actin severing protein gelsolin; the calcium sensitivity of this pathway points to a potential role for neuronal activity in synaptic remodeling ( Pinan-Lucarre et al, 2012 ; Meng et al, 2015 ; Liu et al, 2011 ).…”
Section: Introductionmentioning
confidence: 99%
“…In axon regeneration, elevation of calcium concentration upon injury can activate CED-4 to promote axonal regrowth (Pinan-Lucarre et al, 2012). The second gelsolin domain of GSNL-1 can change its conformation upon binding with calcium to regulate its F-actin severing ability (Liu et al, 2011). These findings suggest that change in local calcium concentration either by neuronal activity or ER/mitochondrial release may modulate the strength of the CED-GSNL-1 pathway in synapse elimination.…”
Section: Discussionmentioning
confidence: 99%
“…Microscopic observation of actin filament severing was performed as described previously [ 20 , 36 ]. Preformed F-actin (5 μM) was incubated with 100 or 200 nM ABP29 or ABP135 G1-G3 in the presence of various concentrations of free Ca 2+ at room temperature for 30 min, and the reaction mixtures were labeled with Alexa 488-phalloidin (Molecular Probes Invitrogen), as previously described [ 6 ].…”
Section: Methodsmentioning
confidence: 99%